Student Affairs : Experiencing Higher Education. - Andres, Lesley; Finlay, Finola (Vancouver : University of British Columbia Press, 2004)
This collection reveals how much institutional change has occurred in the social organization of postsecondary education, and how much more change is required to achieve equitable access and inclusion.
Intro -- Contents -- Foreword -- Acknowledgments -- Student Affairs -- Introduction: Today's Post- Secondary Students - Adding Faces to Numbers -- 1 Equity in Access and Outcomes: Succeeding along the Science Pipeline -- 2 It's No Five O'Clock World: The Lived Experience of Re/entering Mothers in Nursing Education -- 3 A Tunnel of Hope: The Experiences of Student- Mothers Attending a Community- College- Based Developmental Studies Program -- 4 Visitors in the Classroom: The Academic Experiences of Students Who Are Hard of Hearing -- 5 Disciplinary Affiliation and the Experience of Community among Undergraduate Students -- 6 Co-op Education: Access to Benefits or Benefits to Access? -- 7 The Four Rs Revisited: Some Reflections on First Nations and Higher Education -- 8 Welcome to Canada? The Experiences of International Graduate Students at University -- 9 The Transition from High School to Post- High- School Life: Views of the Class of ' 88 -- Conclusion: From Research to Action -- Contributors -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: College students -- British Columbia; Education, Higher -- British Columbia; Academic achievement -- British Columbia; College environment -- British Columbia; Electronic books